2008
DOI: 10.1007/s00414-008-0289-4
|View full text |Cite
|
Sign up to set email alerts
|

Variants of the melanocortin 1 receptor gene (MC1R) and P gene as indicators of the population origin of an individual

Abstract: The population origin of an individual is often requested to be determined from specimens left at a crime scene for identifying a suspect and individual identity. The melanocortin 1 receptor gene (MC1R) and P gene are associated with human pigmentation. Although several studies have reported that these genes are highly polymorphic in human populations, it is unclear if the allele variants can be used to determine the population origin of an individual. We aimed to determine the ethnic origin of an individual b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(36 reference statements)
1
1
0
Order By: Relevance
“…However, no marked linkage disequilibrium was found between rs3791874 and rs16858977. Given this, we supposed that rs3791862 was a newly formed SNP and might evolve because of gene-tic drift or positive Darwinian selection [23,24]. According to this theory, the individuals with heterozygous status at rs3791862 should present a prominent linkage disequilibrium between rs3791874 and rs16858977 and our results verified the hypothesis (D = 0.95).…”
supporting
confidence: 79%
“…However, no marked linkage disequilibrium was found between rs3791874 and rs16858977. Given this, we supposed that rs3791862 was a newly formed SNP and might evolve because of gene-tic drift or positive Darwinian selection [23,24]. According to this theory, the individuals with heterozygous status at rs3791862 should present a prominent linkage disequilibrium between rs3791874 and rs16858977 and our results verified the hypothesis (D = 0.95).…”
supporting
confidence: 79%
“…One recent study set in New Mexico reported carriage of a medium or high risk MC1R variant in 63% of enrolled Hispanics 37 . Some studies have examined associations between MC1R variation and genetic ancestry 38,39 , but there appears to be limited research that also incorporates pigmentation characteristics in Hispanic populations. Our findings contribute novel evidence on the association between MC1R variation and pigmentation characteristics in Hispanics who were not selected to participate on the basis of their personal or family history of melanoma (or non-melanoma skin cancers).…”
Section: Discussionmentioning
confidence: 99%